PENGARUH KEPEMIMPINAN ALTRUISTIK TERHADAP VOICE BEHAVIOR: PERAN MEDIASI KEPERCAYAAN KEPADA PEMIMPIN - Kumala Sari, Anita Dewi; Abdillah, Muhammad Rasyid; Munthe, Richa Afriana (Jurnal Daya Saing, 2026)
This study aims to explore the impact of altruistic leadership on voice behavior and evaluate the mediating role of trust in the leader, considering the significance of voice behavior as a driver of innovation and organizational performance improvement. This study focuses on the impact of altruistic leadership on voice behavior through the mediation of trust in the leader among civil servants (ASN) in Indragiri Hilir Regency. To examine the causal relationship between variables, a quantitative approach with a causal design was used. The population consists of active civil servants, with a sample of 152 respondents selected using purposive sampling to include relevant elements. The main instrument was a questionnaire that measured respondents' perceptions of the variables of altruistic leadership, trust in the leader, and voice behavior. It was found that altruistic leadership positively and significantly influences both voice behavior and trust in the leader, with trust in the leader also positively influencing voice behavior. The key finding is that trust in the leader fully mediates the relationship between altruistic leadership and voice behavior, indicating that a leader's authentic altruistic behavior can only enhance employees' willingness to speak up when it successfully establishes a solid foundation of trust, acting as a psychological buffer against potential risks. The implications of these findings emphasize the urgency for organizations to develop altruism-based leadership as a foundational strategy to build trust, ultimately supporting a participatory and innovative culture.